2022
DOI: 10.3390/polym15010182
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Porous Organic/Inorganic Hybrid Polymers Based on Polyhedral Oligomeric Silsesquioxane for Energy Storage and Hydrogen Production from Water

Abstract: In this study, we used effective and one-pot Heck coupling reactions under moderate reaction conditions to construct two new hybrid porous polymers (named OVS-P-TPA and OVS-P-F HPPs) with high yield, based on silsesquioxane cage nanoparticles through the reaction of octavinylsilsesquioxane (OVS) with different brominated pyrene (P-Br4), triphenylamine (TPA-Br3), and fluorene (F-Br2) as co-monomer units. The successful syntheses of both OVS-HPPs were tested using various instruments, such as X-ray photoelectron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…with the electrolyte. [59][60][61][62][63] The current densities increased upon increasing the scan rate without altering the morphologies of the CV curves, validating the high-rate capabilities, stabilities, and kinetic properties of the TPA-DHTP-BZ POP before and after ROP. Furthermore, we examined the charge/discharge trends and capacitances of these compounds at various current densities [Fig.…”
Section: Polymer Chemistry Papersupporting
confidence: 58%
“…with the electrolyte. [59][60][61][62][63] The current densities increased upon increasing the scan rate without altering the morphologies of the CV curves, validating the high-rate capabilities, stabilities, and kinetic properties of the TPA-DHTP-BZ POP before and after ROP. Furthermore, we examined the charge/discharge trends and capacitances of these compounds at various current densities [Fig.…”
Section: Polymer Chemistry Papersupporting
confidence: 58%
“…This energy source and storage support the advent of electronic products, and the energy relies primarily on the supply of the natural environment [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Renewable energy sources include solar and wind power, ocean energy, hydropower, and biomass; limited energy sources come from industrial fossil fuels such as coal, natural gas, and oil [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. The pursuit of green environmental protection without affecting the life experience of most consumers, or how to ensure the supply and demand of energy while improving economic effects, is a heavy part of technology today.…”
Section: Introductionmentioning
confidence: 99%
“…Polyhedral oligomeric silsesquioxanes (POSS, (R-SiO 1.5 ) n , n = 6, 8, 10, 12, etc. ), are one class of nanosized hybrid nanoblocks of interest in many research areas, including self-organized system-related materials, polymer nanocomposites, and inorganic–organic hybrid functional coatings. With the rigid three-dimensional (3D) configuration, high reactivity, and hybrid nature, , in particular, an intriguing feature of similarity to the secondary building units of zeolites, POSS have also been considered as ideal nanoblocks to develop advanced HPPs. , To date, many studies on the geometry effect of aromatic linking units, such as linear-, planar-, tetrahedral-, propeller-, and ladder-like units, ,, have revealed that the topological combination of POSS with these linking units can tune the porosity and yield various POSS-based porous materials (PPMs) with high performance. However, most studies on PPMs focused on T 8 POSS, and studies on the geometry effect of larger POSS such as T 10 , T 12 , and other compounds are limited (Figure a).…”
Section: Introductionmentioning
confidence: 99%